Droit, informatique et linguistique - Schwab, Wallace (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
Mixing computer technology and linguistic savy as an aid to legal research is no mean undertaking, yet it is the purpose of this article. In it Wallace Schwab attempts to describe those areas in computer science and applied linguistics that either have much to offer or represent formidable obstacles to computerizing legal research. From the simplest aids up through scripts and other artificial intelligence devices, the main theme focusses upon integrating disparate techniques into one finely tuned instrument for linguistically based computer research in law. Ultimately this article leads up to the question as to what limit can be ascribed to digitizing legal data and Schwab proposes short, medium and long term limitations.